2017
DOI: 10.1007/s12072-016-9778-6
|View full text |Cite
|
Sign up to set email alerts
|

Ledipasvir/sofosbuvir without ribavirin is effective in the treatment of recurrent hepatitis C virus infection post-liver transplant

Abstract: Ledipasvir/sofosbuvir without ribavirin is an effective treatment of recurrent hepatitis C virus infection post-liver transplant. The entire group achieved sustained viral response at 12 weeks irrespective of the length of treatment. The combination of ledipasvir/sofosbuvir was well tolerated without serious adverse effects or discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Except one study that did not report patient ethnicity, the majority of patients were Caucasian, male, with a mean age of approximately 60‐year‐old, had GT1a HCV recurrence, and received tacrolimus as part of their immunosuppressive treatment. Five different DAA combination protocols were described: SOF/SMV with or without RBV (n = 8); SOF/LDV (n = 3); ASV/SMV (n = 2); DCV/SMV with or without RBV (n = 2); PrOD (n = 1) . Detailed baseline characteristics of the included studies are provided in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…Except one study that did not report patient ethnicity, the majority of patients were Caucasian, male, with a mean age of approximately 60‐year‐old, had GT1a HCV recurrence, and received tacrolimus as part of their immunosuppressive treatment. Five different DAA combination protocols were described: SOF/SMV with or without RBV (n = 8); SOF/LDV (n = 3); ASV/SMV (n = 2); DCV/SMV with or without RBV (n = 2); PrOD (n = 1) . Detailed baseline characteristics of the included studies are provided in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…The American Association for the Study of Liver Diseases (AASLD) recommends the combination of ledipasvir/sofosbuvir (LDV/SOF) and RBV for 12 weeks for the treatment of HCV infection in LT recipients 19. We showed that the use of LDV/SOF without RBV is effective in achieving SVR 16. Since the data regarding the effect of this regimen on GFR in LT recipients is limited, we performed an ad hoc analysis to determine changes in the GFR with HCV treatment in LT recipients.…”
Section: Introductionmentioning
confidence: 95%
“…The newly introduced direct-acting antiviral agents (DAAs), administered with or without ribavirin (RBV), have revolutionized the treatment of recurrent HCV infection postLT, producing high sustained viral response (SVR) rates 1416. This is important as HCV infection has been found to be a risk for developing renal insufficiency in the LT recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) infection is the leading indication for liver transplantation (LT) in the United States . In 2013, the advent of all‐oral, interferon‐free direct‐acting antivirals (DAAs) transformed treatment options for HCV‐infected (HCV+) patients, and numerous studies have demonstrated the safety and efficacy of DAAs both pre‐ and post‐LT . With the approval of DAAs, providers were faced with the challenge of deciding whether to initiate treatment of HCV+ transplant candidates pre‐ or post‐LT.…”
Section: Introductionmentioning
confidence: 99%